NATO in The Very Cold War: Why the US Needs Nato in the Arctic - Sharon Sebastian Effendy; Bernadeth Franchika; Vanessa Anthea Kusuma (Jurnal Sentris, 2021)
Global warming and climate change resulting in the melting of sea ice within the Arctic have subsequently opened the possibility to explore and exploit the region. Previously seen as simply a region full of ice, the Arctic is believed to possess abundant natural resources, with an estimated 13% of undiscovered oil, 30% of natural gas resources in the world, as well as the opening of a new sea route which will be able to serve as a shortcut for countries to exchange goods - attracting states to pay closer attention to the region, be it militarily, politically, or economically, the United States being one of them. The increase in presence and power among Arctic and non-Arctic countries, especially Russia and China, has inarguably created a state of security dilemma among all parties involved, which is why if the US would like to seek a larger presence within the region, it becomes important for the country to involve NATO as one of its key partners, despite issues concerning the country and the organization. For the purpose of this paper, the aforementioned argument will further be supported using concepts of security dilemma, hegemonic stability theory, and the balance of threat.